The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1977
DOI: 10.1007/bf02256460
|View full text |Cite
|
Sign up to set email alerts
|

Unusual causes of gastrocolic fistula

Abstract: Abstract. 1. Three cases of gastrocolic fistula of unusual cause are presented. These include one patient each with carcinoma of the left kidney, gastric lymphoma, and granulomatous colitis.2. The relationships between the kidneys and gastrointestinal tract are illustrated by a cadaveric crosssection.3. The wide variety of diseases resulting in gastrocolic fistula is discussed.4. Careful fluoroscopic and radiographic study may be necessary to detect the site of the fistula and to identify its cause.Key words: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 14 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…A 2005 review of the literature concluded that <20 entero-entero fistulae secondary to lymphoma had been reported primarily treated surgically [ 6 ]. These intra-abdominal internal lymphomatous fistulae are more commonly jejuno-colic or gastro-colic [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 2005 review of the literature concluded that <20 entero-entero fistulae secondary to lymphoma had been reported primarily treated surgically [ 6 ]. These intra-abdominal internal lymphomatous fistulae are more commonly jejuno-colic or gastro-colic [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%